Effects of metal binding on solubility and resistance of physiological prions depend on tissues and glycotypes. Issue 12 (15th October 2013) - Kuczius, Thorsten; Kelsch, Reinhard
ABSTRACT Prion diseases entail the conversion of a normal host‐encoded prion protein (PrPC) into an infectious isoform (PrPSc). Various PrPC types differing in banding profiles and detergent solubility are present in different tissues, but only few PrPSc types have been generated although PrPC acts as substrate. We hypothesize that distinct PrPC subtypes may be converted more efficiently to PrPSc than others. One prerequisite for the analysis is the identification of the PrPC subtypes present in the protein complexes. Metal binding to PrPC is one of the most prominent features of the protein which induces increased proteolysis resistance and structural changes which might play an important role in the conversion process. Here we analyzed the metal‐induced structural PrPC transformation of two different Triton X‐100 soluble PrPC types derived from human platelets and brains by changes in protein solubility. We found that zinc and copper rendered approximately half of total PrPC and mainly un‐ and low‐glycosylated PrPC to the Triton insoluble fraction. Our results indicate the presence of at least two distinct PrPC subtypes by metal interactions. The differentiation of high and low soluble metal bound PrPC offers precious information about PrPC protein composition and provides approaches for analyzing the transformation efficiency to PrPSc. J. Cell. Biochem. 114: 2690–2698, 2013. © 2013 Wiley Periodicals, Inc.